If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -3x = 10x + 2 Reorder the terms: 6 + -3x = 2 + 10x Solving 6 + -3x = 2 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 6 + -3x + -10x = 2 + 10x + -10x Combine like terms: -3x + -10x = -13x 6 + -13x = 2 + 10x + -10x Combine like terms: 10x + -10x = 0 6 + -13x = 2 + 0 6 + -13x = 2 Add '-6' to each side of the equation. 6 + -6 + -13x = 2 + -6 Combine like terms: 6 + -6 = 0 0 + -13x = 2 + -6 -13x = 2 + -6 Combine like terms: 2 + -6 = -4 -13x = -4 Divide each side by '-13'. x = 0.3076923077 Simplifying x = 0.3076923077
| 19=6+x | | 65x+9= | | 2n-14=-7+3n | | 8m-18=17+m | | 2t+9=17 | | -1.144=1-3.2a+4.54a | | 7m-24=-18+5m | | 8x-(3-x)= | | 3(2)x+1y=7 | | N(N-24)=-128 | | 9p-4=8p | | 2r(r-7)+8r=56 | | 3y-7=-13+y | | -8/3= | | 5(3+6x)-5=130 | | 7(9x+2)=63x-9 | | x+.20x=24 | | 5z-27=2z | | .17a+7=2 | | 44=4(2y+3) | | v^2=-2v+24 | | .5a+5=-4 | | z^3-7z^2+10z=0 | | .04x+.03(5000-x)=180 | | z=m^2-m(1-SQRT(-1))-3(2+SQRT(-1)) | | 2j=64 | | 2j=6473554256376468578575364262 | | factorisex^2-1-42=0 | | 5(d+15)=90 | | 0=x-11-2x | | 12x+10=12x-8 | | x^2-1-42=0 |